Improvement of carotenoid extraction from a recently isolated, robust microalga, Tetraselmis sp. CTP4 (chlorophyta) - Lisa Schueler, Lisa M. Schueler (2021)
In recent years, there has been increasing consumer interest in carotenoids, particularly of marine sustainable origin with applications in the food, cosmeceutical, nutritional supplement and pharmaceutical industries. For instance, microalgae belonging to the genus Tetraselmis are known for their biotechnologically relevant carotenoid profile. The recently isolated marine microalgal strain Tetraselmis sp. CTP4 is a fast-growing, robust industrial strain, which has successfully been produced in 100-m3 photobioreactors. However, there are no reports on total carotenoid contents from this strain belonging to T. striata/convolutae clade. Although there are several reports on extraction methods targeting chlorophytes, extraction depends on the strength of cell coverings, solvent polarity and the nature of the targeted carotenoids. Therefore, this article evaluates different extraction methods targeting Tetraselmis sp. CTP4, a strain known to contain a mechanically resistant theca. Here, we propose a factorial experimental design to compare extraction of total carotenoids from wet and freeze-dried microalgal biomass using four different solvents (acetone, ethanol, methanol or tetrahydrofuran) in combination with two types of mechanical cell disruption (glass beads or dispersion). The extraction efficiency of the methods was assessed by pigment contents and profiles present in the extracts. Extraction of wet biomass by means of glass bead-assisted cell disruption using tetrahydrofuran yielded the highest amounts of lutein and β-carotene (622 ± 40 and 618 ± 32 µg g-1 DW, respectively). Although acetone was slightly less efficient than tetrahydrofuran, it is preferable due to its lower costs and toxicity.